A simple packet combining technique in frequency-hopped spread-spectrum multiple access communication networks - Jik Dong Kim; Sang Wu Kim (1997 IEEE International Conference on Communications, 1997)
In this paper, we propose a simple packet combining scheme in frequency-hopped spread spectrum multiple access (FH/SSMA) communication networks, which makes a tone-by-tone logical AND operation on the previously combined packet and the currently received (retransmitted) packet. The packet error probability is analyzed in the presence of multiple access interference (MAI) with AWGN or Rayleigh fading. It is found that the number of simultaneous users can be increased almost by a factor of two as compared to the conventional scheme, and the performance improvement becomes more significant, as the number of combined packets is increased. It is also found that for the packet error probability of 10/sup -2/ and M=8, a 2-4 dB gain in E/sub b//N/sub 0/ can be obtained over the conventional scheme in the AWGN and Rayleigh fading channels, and the gain increases as M increases.